Rho A and Rac1: Antagonists moving forward - Salloum, Gilbert (2020)
Cells detect external stimuli through cell-surface receptors. In cases where the stimulus is a cytokine or a growth factor, the cell responds by inducing modifications in the actin cytoskeleton. These changes are mediated through the Rho family of GTPases. Among these GTPases, RhoA, Rac1 and Cdc42 have been extensively studied. The activity of these proteins is closely monitored and tightly regulated through Guanine-nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs) that turn the “switch” on and off respectively. Crosstalk between Rho GTPases has been long studied; yet many questions are raised regarding the spatiotemporal regulation of these GTPases, particularly RhoA and Rac1. This review sheds a light on the antagonistic relationship between both GTPases and puts emphasis on the importance of cycling of RhoA activation at the focal adhesions for optimal cell migration.